Literatur Review Perpajakan Deviden Yang Terideks Scopus Tahun 2021-2024 - Richi Guali Padang; Ida Farida Adi Prawira (AKUNTANSI 45, 2025)
This study aims to describe recent developments in dividend tax research, focusing on the identification and analysis of relevant articles. A qualitative descriptive method is used with a literature review approach, utilizing data from Scopus, which includes 17 articles published between 2021 and 2024. The data were collected using the keyword "Dividend Tax" and analyzed to identify current research trends. The results show that the majority of studies on dividend tax utilize the difference-in-differences (DID) method, with six articles employing this approach. These studies focus on various aspects, such as dividend tax reform as an economic policy instrument, the impact of dividend tax on investment efficiency, the effect of dividend tax on investor behavior, and its influence on the market. Emerging research trends indicate that current attention is shifting towards utilizing tax incentives, better corporate governance, oversight in tax utilization, and the long-term investment prospects. This research contributes significantly to understanding the impact of dividend tax on the economy and illustrates the future direction of tax policies that may influence taxation practices and investment decisions across sectors.